A estrutura psicótica e o laço social: o lugar do real na estruturação subjetiva e suas ressonâncias no coletivo - Nunes, Henrique Riedel (2022)
The present thesis investigates how the psychotic condition – considered in lacanian terms as out-of-discourse – can evidence the real’s topology in the psychic constitution and its resonances in collective life. This purpose was the corollary of a previous research trajectory in which aspects of psychosis linked to the superego, the Other and the foreclosure of the Name-of-the-Father were worked on. We came across, then, with the following questions: Would there be an floreclusive statute to the structure itself? Could we conceive in culture, in the social bond and consequently in the discourses something related to an out-of-discourse matrix such as the one attributed to who is structured as psychotic? We seek to identify, through what such structure can show, what is not assimilated from the real in the very process of psychic constitution and, consequently, persists returning from outside in the individual and collective fields. We undertook, then: the rescue of the conclusions and questions worked in our previous researches; a resumption of the works of Freud and Lacan and their clinical dimensions, in order to, with that, seek to collect what precipitates from the psychotic structure as a fact of structure; the reading of contributions from contemporary psychoanalysts, especially Alain Didier-Weill, regarding the problem of foreclosure in its connection with the voice and the superego, as well as in terms of the notion of unforgettable signifier and that of the deaf point, proposed by Jean-Michel Vives. Starting from the discussion about the anteriority of the symbolic as a precedent to subject’s advent, we explore different readings about the primordial operations of subjective constitution – such as: Bejahung, Ausstossung, Vewerfung – showing to what extent the speaking subject is constituted orbiting an extimity. We were able, from such reflections, to attribute to the superego the privileged condition of the return of the foreclosed, so that, through the voice – object of which the sender and receiver are confused – there is the exposure of the subject to a pure synchrony – characteristic of hallucination and fascination. We brought this discussion to the Other’s notion in the field of psychoses and its possible oppositions to collective life, starting from Lacan's 4 discourses as expressions of the social bond, as well as the fifth discourse - that of the capitalist. Finally, we make use of the idea of the discourse of stupidity, constituted from vociferations - a notion proposed by Mauro Mendes Dias – as a manifestation of a bond in collective life that points to the inhuman, that is, what is real irreducible to the subject constituted from language. There is, therefore, in some configurations of the mass, a freezing in front of a signifier, as evidenced by psychosis.